Diabetes and dental implants: The importance of osseointegration in treatment success (Research, Society and Development, 2023)
Osseointegration is a fundamental process for the success of controlled implants in patients with diabetes. Diabetes is a chronic disease that affects glucose metabolism in the body and can affect oral health. Diabetic patients may be at an increased risk of complications during dental procedures, including the placement of purchased implants. The purpose of this article is to highlight the importance of osseointegration in the success of controlled implants in patients with diabetes. The methodology used is a literature review, with the search of 19 scientific articles that met the pre-established inclusion and exclusion criteria, in the Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SCIELO) and the International Health Science Literature (MEDLINE). It is concluded that it is important that diabetic patients are carefully evaluated prior to placement of purchased implants to determine whether they are qualified candidates for treatment. Proper control of blood sugar levels is crucial to minimize the risk of complications and ensure proper osseointegration.